Management of acute allergic reactions by dispatching physicians in a Medical Emergency Dispatch Centre. Issue 2 (20th October 2010) - Godet-Mardirossian, Hélène; Goddet, Nathalie-Sybille; Dolveck, François; Baer, Michel; Fletcher, Dominique; Descatha, Alexis
Abstract : Background: Acute allergic reactions often occur in out-of-hospital settings, and some of these reactions may cause death in the short term. However, initial diagnosis, management and processing of acute allergic reactions by Medical Emergency Dispatch Centres are not documented. The aim of the present study was to describe acute allergic reactions and their management by a Medical Emergency Dispatch Centre. Methods: A prospective study was conducted from 20 August 2006 to 5 November 2006 on incoming calls for acute allergic reactions to the Medical Emergency Dispatch Centre for the Hauts de Seine (Paris West suburb, France). The agreement between initial diagnosis (made by dispatching physician) and final diagnosis (made by the physician who later examined the patient), and between initial and final severity, were evaluated using Cohen's weighted κ coefficient. Results: 210 calls were included. The diagnoses made by the dispatching physician were: in 58.1% of cases urticaria, in 23.8% angioedema, in 13.3% laryngeal oedema, and in 1.9% anaphylactic shock. The agreement between initial and final diagnoses was evaluated by a κ coefficient at 0.44 (95% CI 0.26 to 0.61) and the agreement between initial and final severity was evaluated using a κ coefficient at 0.37 (95% CI 0.24 to 0.50). Conclusions: Only moderate agreement is highlighted between the initial severity assessed by the dispatching physician and the final severity assessed by the physician later examining the patient. This demonstrates the need to develop a tool for assessing severity of acute allergic reactions for dispatching physicians in Medical Emergency Dispatch Centres.